THE INFLUENCE OF CUSTOMER LOYALTY ON INCREASING THE MARKET SHARE OF BANKING INDUSTRY - PHE, CIA; SUTRISNO, NUNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted with the aim of determining the influence of Customer Knowledge, Customer Orientation, Customer Advocacy, and Customer Engagement on Customer Loyalty among Bank Mandiri Savings customers in Jakarta. The data collection technique used in this research was through a survey. Data analysis uses quantitative research and uses a causal research design. The sampling method is non-probability sampling, with purposive sampling technique. Where each variable measurement uses a 5 point Likert scale. This research uses primary data, where all sample data obtained through distributing questionnaires totaled 142 respondents and the data obtained will be processed using SPSS 25 (Statistical Program for Social Science) software. The data analysis method used in this research is multiple linear regression. It is hoped that this research can provide input to banking companies, especially Bank Mandiri, which is the object of this research, so that they can increase their market share in the banking industry in Indonesia